2001
DOI: 10.1080/03079450120078707
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of water-in-oil-in-water emulsion vaccines containing Newcastle disease virus haemagglutinin-neuraminidase glycoprotein

Abstract: Subunit vaccines containing haemagglutinin-neuraminidase (HN) glycoprotein of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…(Snippe et al, 1981; Shakya and Nandakumar, 2013), and RHEODOL AO-15V (sorbitan sesquioleate) (Fukanoki et al, 2000, 2001). Three of these five compounds (i.e., ethanol, gum arabic, and RHEODOL AO-15V) were used to prepare the nanoemulsion W805EC, the OW-14 emulsion, and a water-in-oil-in-water emulsion, respectively (Fukanoki et al, 2000, 2001; Das et al, 2012; Galliher-Beckley et al, 2015) and showed their adjuvant effects as part of these emulsions; however, the adjuvant effect of each compound per se has not previously been shown. To our knowledge, this is the first report to demonstrate their adjuvanticity outside of an emulsion formulation.…”
Section: Resultsmentioning
confidence: 99%
“…(Snippe et al, 1981; Shakya and Nandakumar, 2013), and RHEODOL AO-15V (sorbitan sesquioleate) (Fukanoki et al, 2000, 2001). Three of these five compounds (i.e., ethanol, gum arabic, and RHEODOL AO-15V) were used to prepare the nanoemulsion W805EC, the OW-14 emulsion, and a water-in-oil-in-water emulsion, respectively (Fukanoki et al, 2000, 2001; Das et al, 2012; Galliher-Beckley et al, 2015) and showed their adjuvant effects as part of these emulsions; however, the adjuvant effect of each compound per se has not previously been shown. To our knowledge, this is the first report to demonstrate their adjuvanticity outside of an emulsion formulation.…”
Section: Resultsmentioning
confidence: 99%
“…The vaccines are normally prepared in emulsions of mineral oil (water-in-oil) and administered intramuscularly or subcutaneously. It is generally required that the ratio of water phase to oil phase strikes a balance between the vaccine stability and its viscosity, such that the vaccine remains stable and yet not difficult to administer due to high viscosity of the emulsion [ 136 ]. Because these vaccines cannot replicate and spread horizontally among the vaccinated birds, they are not suitable for mass application.…”
Section: Vaccination Strategiesmentioning
confidence: 99%
“…In addition, an adjuvant formulation consisting of 35% v/v squalene emulsion emulsified with 15% v/v Arlacel ® A (mannide monooleate) mixed with a polycationic polyelectrolyte has been described [ 104 ]. Also of interest, a water-in-oil-in-water (w/o/w) squalene adjuvant was found to be safe and effective in protecting chickens against Newcastle disease virus [ 105 ]. It is composed of liquid paraffin (25%), squalene (10%), diglyceryl monooleate (5%), and Tween ® 80 (2%) in PBS.…”
Section: Vaccinesmentioning
confidence: 99%